Biblical Texts in Digitalization Towards Critical Digital Biblical Studies - Al-Suadi, Soham; Ulshöfer, Gotlind (Tübingen University Press, 2021)
Digitization is also becoming increasingly important for the processing and presentation of biblical texts and their manuscripts. While digitization promises egalitarian access to resources on the one hand, it also poses new challenges in research and teaching on the other. Digital methods and the experiences made with them in the Digital Humanities are also of interest for theology. The anthology focuses on forms of digitized handling of biblical texts and their manuscripts, such as Codex Sinaiticus. It deals with tools of computational philology or computational linguistics as well as with "digital research environments" and the effects of digitization with regard to the use and handling of biblical texts. The articles in this conference volume cover biblical-theological, exegetical, historical, systematic-theological and information-scientific aspects and are in English and German.